1965
DOI: 10.1073/pnas.54.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally induced activation of the ribosomes of the unfertilized sea urchin egg.

Abstract: ZOOLOGY: MONROY ET AL. 107 recipient eggs, and none of these eggs developed normally. These results indicate a real difference in the "developmental capacity" of germ cell and somatic cell nuclei. Many of the germ cell nuclei are shown to be developmentally totipotent, while by the same test the somatic nuclei are shown to be severely restricted in capacity to promote development. The author is very grateful to Dr. Robert Briggs for his advice during the course of this investigation and for his suggestions dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1966
1966
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…In these latter systems the increase in microsomal acti'vity results from the formation of active complexes between rilbosomes and pre-existing imssenger RNA and not from the formation of new messenger RNA (26,29). T'he evidence 'for this conclusion is 'particularly clear in the case of the sea-urchin egigs ibecause RNA synthesis is not detectable after fertilization until the blastula stage (6).…”
Section: Discussionmentioning
confidence: 99%
“…In these latter systems the increase in microsomal acti'vity results from the formation of active complexes between rilbosomes and pre-existing imssenger RNA and not from the formation of new messenger RNA (26,29). T'he evidence 'for this conclusion is 'particularly clear in the case of the sea-urchin egigs ibecause RNA synthesis is not detectable after fertilization until the blastula stage (6).…”
Section: Discussionmentioning
confidence: 99%
“…Such difficulties in obtaining homogeneous size fractions from gradients for electron microscopy have been well described by Mathias, Williamson, Huxley & Page (1964). Nevertheless, the existence of a special class of polysomes differing from others in its sensitivity to ribonuclease in vitro, and to actinomycin D in zlivo, suggests that particular m-RNA's may be 'stored' in the cytoplasm (see Monroy et al 1965) and then 'activated', whilst others are continuously translated and degraded. Although specific control of translation does appear to occur in higher organisms, and indeed in view of the stability of m-RNA it might be of extreme importance, we have as yet little idea as to how such control is actually effected.…”
Section: The Control Of Specific Protein Synthesis In Higher Animmentioning
confidence: 97%
“…The inhibitor is thought to be present in larger amounts in microsomes from adult liver than in those from regenerating liver. It is interesting to note that Hoagland et al (1964) find no inhibition of the binding of 14C-polyuridylic acid, a synthetic m-RNA, to ribosomes in the presence of the inhibitor, but whether this binding in the presence of inhibitor is of the normal functional ribosome-m-RNA type is unknown (Monroy et al 1965). Tsukada & Lieberman (1965a) claim that polysomes from regenerating rat liver owe their greater stability and activity to their containing a phospholipase A-resistant component, absent from polysomes of adult liver.…”
Section: )mentioning
confidence: 99%
“…For example, egg ribosomes can translate added poly(U) even though they display little intrinsic protein synthetic activity (Nemer 1962;Wilt and Hultin 1962). Deproteinized egg RNA can be translated in a cell-free system (Maggio et al 1964;Monroy et al 1965) and cytoplasmic messenger ribonucleoprotein (mRNP) particles were observed (Spirin and Nemer 1965). Because the assembly of masked mRNP complexes must take place during oogenesis, the sea urchin system exemplifies a reversible process of mRNA repression and activation.…”
Section: Sea Urchin Eggsmentioning
confidence: 99%